Domestic Architecture of Raul Lino (1900-1918): Expression of the meridional Arts and Crafts, or local synthesis of a universal artistic movement of the last third of eight hundred - Pereira, Paulo Manta (A Casa Senhorial em Lisboa e no Rio de Janeiro (séculos XVI, XVII, XVIII e XIX): Anatomia dos Interiores, 2014)
In six hundred, the Manor House reflects the enrichment of aristocracy based on the exploitation of coffee and gold, with major expression in the metropoles of Lisbon and Rio de Janeiro. In seven hundred, the Johannine baroque house become autonomous from the circumstance without corresponds to the higher fortune of design and tectonics of the facade, equal dynamics in the organization of space. In eight hundred, the Manor House becomes bourgeois, standardized and internationalized to the taste of french eclectic design. Formed in the last decade of eight hundreded between Windsor and Hanover, contaminated by German Romanticism and English Arts and Crafts, Raul Lino opposed to the zeitgeist of progress a dialectic of continuity with tradition. At Portugal in the first half of the twentieth century, theorizes and design the organization of domestic architecture centered on the atrium, radiating outwards, pedagogy of modernity that we analyze trough Monsalvat House (1901), O’Neill House (1902 -1918) and the Cypress House (1912-1914).